If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -8 = 3n + 4 Reorder the terms: -8 + 7n = 3n + 4 Reorder the terms: -8 + 7n = 4 + 3n Solving -8 + 7n = 4 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -8 + 7n + -3n = 4 + 3n + -3n Combine like terms: 7n + -3n = 4n -8 + 4n = 4 + 3n + -3n Combine like terms: 3n + -3n = 0 -8 + 4n = 4 + 0 -8 + 4n = 4 Add '8' to each side of the equation. -8 + 8 + 4n = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 4n = 4 + 8 4n = 4 + 8 Combine like terms: 4 + 8 = 12 4n = 12 Divide each side by '4'. n = 3 Simplifying n = 3
| -10y-2y=64 | | -16x^2-x+225=0 | | 8+7x-5-2x= | | 2x+6=3x+8 | | 7a+2=-26 | | 5(6x+3)=3(2x-2) | | x^4-5x^3=14x^2 | | 6b+10=-2 | | 7x-3x^2=2 | | 7x-36=6x+3 | | 6y+6=18 | | -16x^2+80x=100 | | -4x+9=-39 | | b/1+6=2 | | -x+6=-21+8x | | u=3(5-u)+1 | | 4+6x=-62 | | 3(3x-4)=2x-8 | | 4t+3(2-t)=13 | | 2+7x=-5 | | -6(3x+6)+2= | | 3x+4=-5+2x | | -7x-8=-71 | | -7-2x=-9 | | (2t^2-t-6)(2t^2+2t-1)= | | 7(2y-3)=-16 | | -5+4x=35 | | 40+35=b | | 5n+8n= | | 64=-16x^2+80x | | 3-p-4+p= | | 3(4x+12)=48 |